Efektivitas Metode Membaca Bersama dalam Meningkatkan Pemahaman Bacaan pada Mata Pelajaran Bahasa Indonesia di Kelas II SDN 13 Telaga Biru - Sri Ayuni; Yurni Rahman; Nur Syaidah (Transbahasa, 2026)
This study aims to analyze the effectiveness of the shared reading method in improving reading comprehension among second-grade students in Indonesian language learning at SDN 13 Telaga Biru and to describe changes in students’ participation and responses during the learning process. This study employed a qualitative descriptive approach. The research subjects consisted of the second-grade teacher and second-grade students of SDN 13 Telaga Biru. Data were collected through observation, interviews, and documentation and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that prior to the implementation of the shared reading method, the learning process was predominantly teacher-centered, resulting in low student participation and difficulties in understanding reading texts. After the shared reading method was implemented through modeling, choral reading, discussion, and reflection activities, students demonstrated significant improvement in comprehending reading materials, identifying key information, and answering questions related to the texts. In addition, students became more active, enthusiastic, and confident during classroom activities. The shared reading method also created a more interactive, collaborative, and enjoyable learning environment. Therefore, it can be concluded that the shared reading method is effective in improving reading comprehension among elementary school students.